A guide to building education partnerships : navigating diverse cultural contexts to turn challenge into promise - Hora, Matthew T., 1972- (Stylus Pub., 2011)
The authors present the diagnostic tools for undertaking a deliberate and research-based approach to planning, designing, and managing a partnership. By surfacing participants' often-differing motivations, and the practices and assumptions they bring to the table, the book provides the foundation for developing a constructive relationship. In scope, the book extends beyond school-university partnerships to include schools' collaboration with state and local governments, nonprofit organizations, and the business sector.